Gleason Score Evolution and the Effect on Prostate Cancer Outcomes. Issue 5 (20th October 2020) - Swanson, Gregory P; Trevathan, Sean; Hammonds, Kendall A P; Speights, V O; Hermans, Michael R
Abstract: Objectives: We evaluated how the changes in Gleason grading affected the long-term outcomes of a large prostatectomy cohort. Methods: We obtained long-term follow-up (16.7 years) in 581 patients having undergone radical retropubic prostatectomy between 1985 and 1995. We excluded those with seminal vesicle and/or lymphatic involvement. We regraded the specimens according to contemporary guidelines and compared how this affected outcomes compared with their original (pre-1995) Gleason scoring. In total, 499 patients were evaluable. Results: A Gleason score of 6 or less declined from 73% to 29%, and the number increased from 25% to 63% for a Gleason score of 7 and from 5% to 8% for a Gleason score of 8 to 9. As a result, for a Gleason score less than 7, biochemical failure decreased from 28% to 23%, metastatic disease 5% to 2%, and prostate cancer death from 5% to 3%. The same results were 50% to 37%, 11% to 7%, and 10% to 6% for a Gleason score of 7 and 86% to 71%, 43% to 32%, and 29% to 26% for a Gleason score more than 7, respectively. With the most recent grade grouping, for groups 1 to 5, biochemical failure occurred in 23%, 32%, 45%, 69%, and 78%, respectively. Metastatic disease occurred in 2%, 4%, 12%, 24%, and 56%, respectively. Prostate cancer–related death occurred in 2%, 4%, 9%, 21%, and 44%, respectively. Conclusions: The revised Gleason scores improved the outcomes in all risk groups. Based on Gleason score, patients with prostate cancer will appear to have better outcomes than they did before 2005, making any comparison tenable. The current grading system shows a consistent increased risk in biochemical failure, metastatic disease, and prostate cancer–related death with each successive grade.